La responsabilidad de la ciencia en la catástrofe ambiental - Tamayo, Luis (Nómadas. Critical Journal of Social and Juridical Science, 2011)
This essay studies the environmental catastrophe produced by climate change and the depleted of natural resources, also studies the responsibility of science and technology in his generation. At the end we propose some alternatives of mitigation.
Keywords: imperative of responsibility; science; environmental catastrophe